Location Problems with Distribution Capacity and Time Limitations - Karaçeper, Eser (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Locational decisions are generally considered strategical level decisions. Hence, location problems received a large concern in the literature. There are several factors like: distances, demand amounts, facility capacities etc. that may affect the locational decisions. Most studies in the literature had considered these factors. However, there are few studies which considers distribution capacities of the production systems. Today, especially service production systems such as fast-food producers declare a time limit in their delivery operations. In such systems, the distribution capacities and distribution time limits should be considered in location problems. In this study, it is aimed at investigate several realistic versions of location problems with distribution capacity and time limits, formulate these problems as optimization problems and develop exact/heuristic solution methods for those problems. In this study, two distribution capacitated locational problem type had been developed. Type-1 is distribution capacitated version of well-known p-center problem on the other hand, type-2 is distribution capacitated version of well-known maximum-covering problem. MIP models and heuristic algorithms had been developed for both type of the problem. After that, computed results are compared and findings had been presented in conclusion section. In addition, a real life case study had been done too. Keywords: location optimization, distribution capacities, p-center, maximum covering.

ÖZ: Yer seçimi kararları genel olarak stratejik kararlardır. Dolayısıyla yer seçimi kararları üzerine literatürde oldukça fazla sayıda çalışma bulunmaktadır. Uzaklık, talep miktarı, tesis kapasitesi vb. birtakım faktörler yer seçimi kararlarını etkilemektedir. Yukarıda bahsedilen faktörler literatürde birçok çalışmada yer almıştır. Fakat, bir üretimin sisteminin dağıtım kapasitesi düşünülürek yapılan çalışmalar oldukça az sayıdadır. Günümüzde, servis üzerine hizmet veren üretim sistemleri dağıtım operasyonları için zaman kısıtı koymuşlardır. Buna örnek olarak Fast-Food tesislerini verebiliriz. Bu tarz sistemlerde yer seçimi problemi düşünülürken dağıtım kapasiteleri ve dağıtım süreleride hesaba katılmaladır. Bu çalışmanın amacı gerçekçi dağıtım kapasiteli ve zaman kısıtlı yer seçimi problemlerini araştırıp daha sonra bunları çözmek üzere kesin ve sezgisel çözüm yöntemlerini formülüze etmektir. Bu çalışmada dağıtım kapasiteli iki farklı yer seçimi problemi geliştirilmiştir. Tip 1 problemi literatürde bilinen p-center probleminin dağıtım kapasiteli versiyonudur öte yandan Tip 2 probleimi literatürde bilinen maximum-covering probleminin dağıtım kapasiteli versiyondur. Her iki problem tipi içi karışık tamsayı izlenceleme modelleri ve sezgisel algoritmalar oluşturulmuştur. Daha sonra, bulunan sonuçlar karşılaştırılmış ve bulgular sonuç bölümünde yer almıştır. Ayrıca, gerçek hayattan bir vaka çalışması yapılmıştır. Anahtar Kelimeler: yer seçimi eniyilemesi, dağıtımı kapasitesleri, p-center, maximum covering
Master of Science in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2019. Supervisor: Assoc. Prof. Dr. Hüseyin Güden.
Keywords: Industrial Engineering; Production Management; Location optimization; distribution capacities; p-center; maximum covering